Efektivitas Konvergensi Program Intervensi Percepatan Penurunan Stunting di Tingkat Keluarga - Bekti Handayani (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
This study aims to analyze the effectiveness of the convergence of intervention programs to accelerate the reduction of stunting at the family level in Serang District, Banten Province. Analytic quantitative design and interviews, with a sample of 150 respondents. Data collection technique with systematic random sampling. Data collection with secondary data, interviews and filling out questionnaires. There were 9 people (6 percent) inaccurate identification of families at risk of stunting (KRS) in the TPPS documents and verification by researchers. Inaccurate identification of families at risk of stunting who were included in the target of the intervention program between the TPPS documents and the researcher's verification was 8 people (5.3 percent). There were 5 people (3.3 percent) inaccurate identification of stunting-risk families who received intervention programs between TPPS documents and researcher verification. Recording and reporting of interventions is not optimal. There is a gap in the convergence of intervention programs due to several factors, namely inadequate quality of human resources, unstable internet network during data collection, limited time for orientation or training so that it is still conceptual, there are still residents who do not have a family card, lack of budget, non-compliant respondents take blood tablets. Not all of the effectiveness of the convergence of intervention programs has conformity in the documents at TPPS and researcher verification.